2011
DOI: 10.3109/17435390.2011.579631
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, distribution and toxicity of gold nanoparticles in tobacco (Nicotiana xanthi) seedlings

Abstract: Understanding plant interactions with nanoparticles is of increasing importance for assessing their toxicity and trophic transport. The primary objective of this study was to assess uptake, biodistribution and toxicity associated with exposure of tobacco plants (Nicotiana xanthi) to gold nanoparticles (AuNPs). We employed synchrotron-based X-ray microanalysis with X-ray absorption near-edge microspectroscopy and high resolution electron microscopy to localize AuNPs within plants. Results from these experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(113 citation statements)
references
References 34 publications
4
104
2
Order By: Relevance
“…Some reports stated that 40 -50 nm is the size exclusion limit in almost all plants (González -Melendi et al, 2008;Corredor et al, 2009;Sabo-Attwood et al, 2012;Taylor et al, 2014). In addition, o ther factors which influence the uptake of nanoparticles are: the type of nanoparticle, its chemical composition and coating of its surface (Ma et al, 2010;Rico et al, 2011;Judy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports stated that 40 -50 nm is the size exclusion limit in almost all plants (González -Melendi et al, 2008;Corredor et al, 2009;Sabo-Attwood et al, 2012;Taylor et al, 2014). In addition, o ther factors which influence the uptake of nanoparticles are: the type of nanoparticle, its chemical composition and coating of its surface (Ma et al, 2010;Rico et al, 2011;Judy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Size seems to be one of the main restrictions for penetration into plant tissues, and there are some reports about the maximum dimensions that plants allow for nanoparticles to move and accumulate inside the cells, usually with 40-50 nm as a size exclusion limit (González-Melendi et al, 2008;Corredor et al, 2009;Sabo-Attwood et al, 2012;Taylor et al, 2014). Additionally, the type of nanoparticle and its chemical composition is another factor influencing the uptake (Ma et al, 2010;Rico et al, 2011), whereas morphology has also been demonstrated as determinant in some cases (Raliya et al, 2016).…”
Section: Plant Absorption and Uptake Of Nanoparticlesmentioning
confidence: 99%
“…It is also essential to review studies based on size-dependent mechanisms of GNP uptake as smaller particles of about 3.5nm are able to move into the vasculature of the plants from the roots compared to particles of size 18nm that remained agglomerated onto the outer surface of the roots. It was also found that the 3.5nm GNPs caused leaf necrosis after 14 days of exposure in tobacco plants [46].…”
Section: Environmental Fate Of Gnpsmentioning
confidence: 95%